2003
DOI: 10.1034/j.1600-0536.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergic contact dermatitis in a company manufacturing boards coated with isocyanate lacquer

Abstract: Over a short period of time, there was an outbreak of work-related skin lesions among workers at a company producing flooring laminate boards, after the introduction of a water-repellent lacquer based on diphenylmethane-4,4'-diisocyanate (MDI). In 5 workers, patch testing was performed with a standard series, an isocyanate series and work-environmental products when indicated. 3 of the workers were tested with the lacquer, and contact allergy was found with concurrent reactions to 4,4'-diaminodiphenylmethane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 14 publications
1
56
1
Order By: Relevance
“…Both our results and a previous study by Kääriä et al (2001) indicate a poor correlation between airborne exposure to MDI and urinary biomarker levels. This observation could be due to significant dermal uptake of MDA originating from exposure to MDI or MDI-related substances (Brunmark et al 1995, Frick et al 2003. Also, occupationally unexposed subjects have been shown to have significant U-MDA levels, indicating nonoccupational background exposure (Sennbro et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Both our results and a previous study by Kääriä et al (2001) indicate a poor correlation between airborne exposure to MDI and urinary biomarker levels. This observation could be due to significant dermal uptake of MDA originating from exposure to MDI or MDI-related substances (Brunmark et al 1995, Frick et al 2003. Also, occupationally unexposed subjects have been shown to have significant U-MDA levels, indicating nonoccupational background exposure (Sennbro et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, 7 individuals reacted to MDA, despite of lack of confirmed presence of this chemical in occupational setting. In other studies, sensitization to MDA, was frequently found together with contact allergy to MDI and MDA was considered as an indicator of MDI contact sensitization [2][3][4]19,24,25]. Simultaneous reactions to MDI and MDA were attributed to their cross-reactivity related to the similar structure [26], although according to some authors, these two chemicals could have been both primary sensitizers [3].…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, sensitization to MDA, was frequently found together with contact allergy to MDI and MDA was considered as an indicator of MDI contact sensitization [2][3][4]19,24,25]. Simultaneous reactions to MDI and MDA were attributed to their cross-reactivity related to the similar structure [26], although according to some authors, these two chemicals could have been both primary sensitizers [3]. In some reports, as in our study, individuals exposed to MDI did not react to this compound in patch testing, whereas positive reactions were observed to MDA, regardless of the presence or absence of MDA in occupational setting [2,3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations